ANALISIS DETERMINAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI BAGI USAHA KECIL DAN MENENGAH DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOR - Supriono Supriono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
Information technology has an important role in supporting the business processes of a company, including small and medium enterprises. In a large enterprise application of information technology has been widely applied in supporting the progress ofhis business. In contrast to thesmall and medium enterprisesusing information technologywas stilllowin the processto supportbusiness activities. Viewed from the sidebenefits of information technologywillhave a positive impactfor SMEs include improved accessto markets, information, efficiency of production and so forth. In addition,the use of technology by SMEs will bring new business opportunities. This study will analyze the factors that affect the successful implementation of accounting information systems in SMEs Kebumen, using the Theory ofplannned Behaviour(TPB). Respondents in this study amounted to 50 respondents, which consisted of 16 respondents from small business group and 34 respondents from the group of medium-sized businesses.Analysis techniques used in this study is the multiple regression analysis, while the mediating variables used method of causal analysis step. The results ofthis study states that1) attitude positive and significant effecton the interest/intention use of accounting information systems. 2). subjective norm positive and significant effecton the interest in the use of accounting information systems. 3). Perceived behavioral control of significant negative effect on the desirability of using accounting information systems.4)Intention inthe use of SIA positive and significant impacton the use ofAIS. The higher the interest of SMEs in using the higher SIA use.5) Mediating variable interest in the use of AIS does not moderate variable subjective norma gainst the use ofAIS. Moderate interest in the use of AIS perfect mediate variable attitude sand perceptions of behavior alcontrol on the use of AIS Keywords; Accounting Information System, SMEs, TPB